Comparison of somatic cell count influence on mastitis frequency in following lactations in dairy cows of holstein and simmental breed - Cergolj, Marijan (Array, 2006)
Research involved 400 cows of different oweners. 100 cows of Holstein breed were taken from the database that had somatic cell count (SCC) lower than 400, 000 and 100, 000 cows with SCC higher than 400, 000. Cows of simmental breed were chosen in the same way, Cows were divided into groups opon the number of lactations ansd somatic cell count. Cows of Holstein breed and total population of cows with high SCC in previous lactation became more ill in the following lactation than the cows with low SCC (P<0, 05), while in group of cows of simmental breed high SCC in previous lactation had no influence on mastitis appearance in the following one. All groups of cows had least mastitis appearance in third lactation.